Post-COVID-19 functional status in socioeconomically vulnerable neighborhoods attended in primary health care in two Brazilian cities: a cross-sectional study - Danielle Souto de Medeiros; Gabriele Amorim; Fabiane Soares; Laio Magno; Thaís Regis Aranha Rossi; Thiago Silva Torres; Valdiléa Gonçalves Veloso; Débora Castanheira; Inês Dourado (BMC Infectious Diseases)
Abstract Background The prolonged effects of COVID-19 present social costs and pose challenges to public health infrastructure, necessitating the implementation of public policies for comprehensive post-COVID-19 care. Objective This study aimed to assess post-COVID functional status and associated sociodemographic factors and health inequalities among residents of socioeconomically vulnerable neighborhoods who attended primary health care in two Brazilian cities. Methods A cross-sectional study was conducted from July 2022 to July 2023 in Salvador and Rio de Janeiro. We included participants who sought COVID-19 tests in primary health care services, had previously contracted COVID-19, and completed the post-COVID-19 functional status scale. Post-COVID syndrome was classified as none, negligible/slight, or moderate/severe. Sociodemographic characteristics, health conditions, and access to health services were analyzed as explanatory variables. Descriptive and bivariate analyses were performed. Using multinomial logistic regression, we estimated the adjusted odds ratios (aORs) and their 95% confidence intervals (95%CIs). Results Among the 3,067 participants, the overall prevalence of post-COVID functional limitations status was 34.6% (26.7% and 7.9% reporting negligible/slight and moderate/severe, respectively). The following variables were associated with moderate/severe functional status: living in households with fewer rooms (aOR = 1.66, 95%CI: 1.23–2.24), female gender (aOR = 1.57, 95%CI: 1.14–2.16), older age (aOR = 1.02, 95%CI: 1.01–1.03), self-reported diabetes mellitus (aOR = 1.78, 95%CI: 1.17–2.69), respiratory diseases (aOR = 2.59, 95%CI: 1.56–4.29), having contracted COVID-19 two or more times (aOR = 1.57, 95%CI: 1.15–2.14), not having had a medical appointment in the last 12 months (aOR = 1.70, 95%CI: 1.24–2.33), difficulty accessing COVID-19 testing (aOR = 1.63, 95%CI: 1.05–2.52), and experience discrimination in health services (aOR = 2.85, 95%CI: 1.87–4.35). Conclusions Our findings indicate varying degrees of post-COVID functional limitation status among residents of socioeconomically vulnerable neighborhoods who have recovered from COVID-19. People who live in homes with fewer rooms, are female, older, have pre-existing diabetes or respiratory diseases, have been reinfected with COVID-19, have difficulty accessing COVID-19 testing and those who experienced discrimination in health services are at higher chance of developing post-COVID syndrome.